Multi‐Control of Ion Transport in a Field‐Effect Iontronic Device based on Sandwich‐Structured Nanochannels. (20th November 2022) - Wu, Rong; Hao, Junran; Cui, Yanshuai; Zhou, Jiale; Zhao, Danying; Zhang, Shangtao; Wang, Jian; Zhou, Yahong; Jiang, Lei
Abstract: Biomimetic smart nanochannels can regulate ion transport behavior responsive to the external stimuli, having huge potential in nanofluidic devices, sensors and energy conversion. Field‐effect nanofluidic diodes or transistors based on electric‐responsive nanochannels are emerging owing to their advantages such as non‐invasiveness, in situ, real time, and high efficiency. However, simultaneously realizing the voltage‐control of the ion conductance and ion current rectification (ICR) properties is still a big challenge. Here, a field‐effect iontronic device is developed based on ionomer/anodic aluminum oxide/conducting polymer sandwich‐structured nanochannel to realize the multi‐control of ion transport behaviors including ion conductance, ICR magnitude, and ICR direction by modulating the surface charge, wettability, and morphology of the nanochannel. The electroactive conducting polymer carries tunable surface charges responsive to the electric stimuli, leading to the regulation of ICR values. The complex three‐segment structures lead to the reverse of ICR direction by reconfiguring the charge distribution along with the whole channel. The switching wettability between hydrophilic and hydrophobic results in the regulation of ion conductance. Furthermore, the field‐effect iontronic device functions in a wide salinity range especially in hypersaline environment, due to the salinity‐adaptive properties of the membrane. A new route is provided for designing more functional field‐effect nanofluidic devices. Abstract : A field‐effect iontronic device based on ionomer/anodic aluminum oxide/conducting polymer sandwich‐structured nanochannel is constructed to realize the multi‐control of ion transport behaviors including ion conductance, ion current rectification (ICR magnitude, and ICR direction by modulating the surface charge, wettability, and morphology of the nanochannel. The tunable surface charge of electroactive conducting polymer and complex three‐segment structure contribute to the multi‐control of nanofluidic behaviors.